Effect of Growth Regulators on the Growth and Flowering of Anthurium - Beena R (Department of Plant Physiology, College of Agriculture, 2000)
An investigation on the effect of growth regulators on growth and flowering of Anthurium andreanum Linden was conducted in the Department of Plant Physiology, College of Agriculture, Vellayani during 1998-2000. Mature plants of three varieties of Anthurium andreanum Linden formed the material. The varieties used were Liver Red (L.R.), Ceylon Red (C.R.) and Kalympong Orange (K.O.). Three growth regulators namely Gibberellic Acid (GA), Tri Iodo Benzoic Acid (TIBA) and Kinetin (K) were used at 100 ppm, 300 ppm and 500 ppm concentrations. Two controls i.e., distilled water spray and no spray were also included. Each concentration of the growth regulator was sprayed three times at one month intervals. Observations were taken three months after the first spray and then at three months intervals, twice more. The effect of treatments on morphological floral, physiological and bio-chemical aspects was studied. Results of the experiments revealed that growth regulators had significant effect on most of the characters under study. They are listed below. ;.. Maximum plant height was obtained nine months after the first spray for K.O. treated with GA at 500 ppm (69.82 cm). ;.. Minimum plant spread (EW) - nine months afte~ the first spray was obtained for K.O. treated with TIBA at 100 ppm (28.44 cm) and minimum plant spread (NS) was recorded by K.O. - no spray (28.02 cm) in the ninth month of observation.